Analisis Migrasi Tenaga Kerja Pada Sektor Perekonomian di Kabupaten Tulungagung - Ahmad Zaky Muttaqien; Devi Ayu Widyaningrum; Anggoro Putranto (Journal of Creative Student Research, 2023)
The phenomenon of migration is a phenomenon that is often found in people’s lives as an alternative action to make a move for a specific purpose, including work. Migration is one of the causes of population movement between regions. The development gap between cities and villages continues to be a driving force for migration. It is inevitable that every human being would want to have a comfortable place to live with adequate facilities, for example there are places for entertainment, sports, education, and so on. The era of globalization has also removed barriers for everyone to migrate between countries and even continents. International migration of labor can be interpreted as the movement of individuals from one country to another with the aim of getting a job. Globalization also makes people to carry out mobility with various reasons they have. Problems with migration also do not include the problems of the destination (recipient) country, but also the country of origin, where after the immigrants return to their country of origin it becomes a problem that must be resolved. priority so that they have a high quality and level of competitiveness as well as gain an understanding of their rights as migrant workers. The results of this study are to obtain information about the number of people migrating out of the Tulungagung Regency area and its impact on the economic sector in the Tulungagung Regency area because migration greatly influences the opportunities and challenges in the region.